2019
DOI: 10.1111/hel.12592
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide antibiotic resistance mapping of Helicobacter pylori in Korea: A prospective multicenter study

Abstract: Introduction The eradication rates for Helicobacter pylori have decreased in Korea although the prevalence of this bacterium has also decreased. Antibiotic resistance is likely to be a crucial factor in H. pylori eradication success, and we therefore mapped these resistance patterns nationwide in Korea. Materials and Methods Five hundred and ninety adult subjects were prospectively enrolled from 2017 to 2018 from 15 centers across six geographic areas of Korea. A total of 580 biopsy tissues had been sampled fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
96
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 30 publications
13
96
3
2
Order By: Relevance
“…Another reason could be the differences in the 15 participating institutes. 44 In fact, we have also reported regional differences in which the MIC study was performed by the SNUBH team by the same technician (NRH) as the present study. 49 This study showed a considerable difference in the antibiotic resistance rate between urban areas and rural areas.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Another reason could be the differences in the 15 participating institutes. 44 In fact, we have also reported regional differences in which the MIC study was performed by the SNUBH team by the same technician (NRH) as the present study. 49 This study showed a considerable difference in the antibiotic resistance rate between urban areas and rural areas.…”
Section: Discussionsupporting
confidence: 49%
“…In contrast, our institute has continuously performed H pylori culture with fresh tissue from multiple biopsy samples with a consistent protocol for the past 16 years, and the culture success rate is approximately 80%. Another reason could be the differences in the 15 participating institutes . In fact, we have also reported regional differences in which the MIC study was performed by the SNUBH team by the same technician (NRH) as the present study .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Furthermore, H. pylori resistance against tetracycline has been low and stable in Korea for the past 16 years . A recent multicenter study showed that the antibiotic resistance rate in H. pylori is lowest in Seoul . In that study, the rate of tetracycline resistance was 0%.…”
Section: Introductionmentioning
confidence: 84%